Implications of Russia's Aggression Against Ukraine for its Membership at the UN Human Rights Council - Vanesha Salsabila Keisya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Russia has engaged in military operations leading to aggression since 2014 on the Crimean peninsula, culminating in Russia opposing Ukraine's desire to join the North Treaty Organization (NATO) in 2022. Russia is a member state in the UN Human Rights Council since 2020, as a result of violating human rights has resulted in Russia's membership status in the UN Human Rights Council being suspended. In accordance with the provisions of the establishment of the UN Human Rights Council through the UN General Assembly Resolution, namely MU-UN Resolution 60/251 entitled